Implementasi Kebijakan Program Posbindu PTM di Wilayah Kerja UPTD Puskesmas Oesapa 2024 - Eufransiani R. Tema; Dominirsep O. Dodo; Masrida Sinaga (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Non-Communicable Diseases (NCDs) are the leading cause of death worldwide, including in the Province of East Nusa Tenggara (NTT) where in 2022 there were 130,084 cases of death due to NCDs. Kupang City reported 10,943 cases. In the Oesapa Health Center area, the most common NCDs found were hypertension and diabetes mellitus. This study examines the implementation of the POSBINDU NCD program using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework. The phenomenological qualitative approach involved seven informants, namely one program manager and six supporting participants. Data collection was carried out through in-depth interviews and observations. This program has succeeded in reaching individuals aged 15–59 years, both healthy and at risk, through activities in the workplace, schools, places of worship, and the community, with the support of local community leaders. POSBINDU was adopted as a tool for early detection, education, and control of NCDs. This program is planned to be continued through Integrated Primary Services (PPT). However, implementation and effectiveness are still limited due to low community participation, few trained health cadres, and inadequate infrastructure (e.g., equipment, health records, documentation). These challenges reduce the quality and impact of services.